The effect of changing plantarflexion resistive moment of an articulated ankle-foot orthosis on ankle and knee joint angles and moments while walking in patients post stroke - Kobayashi, Toshiki (Clin Biomech (Bristol, Avon), 2015)
BACKGROUND: The adjustment of plantarflexion resistive moment of an articulated ankle-foot orthosis is considered important in patients post stroke, but the evidence is still limited. Therefore, the aim of this study was to investigate the effect of changing the plantarflexion resistive moment of an articulated ankle-foot orthosis on ankle and knee joint angles and moments in patients post stroke. METHODS: Gait analysis was performed on 10 subjects post stroke under four different plantarflexion resistive moment conditions using a newly designed articulated ankle-foot orthosis. Data were recorded using a Bertec split-belt instrumented treadmill in a 3-dimensional motion analysis laboratory. FINDINGS: The ankle and knee sagittal joint angles and moments were significantly affected by the amount of plantarflexion resistive moment of the ankle-foot orthosis. Increasing the plantarflexion resistive moment of the ankle-foot orthosis induced significant decreases both in the peak ankle plantarflexion angle (P<0.01) and the peak knee extension angle (P<0.05). Also, the increase induced significant increases in the internal dorsiflexion moment of the ankle joint (P<0.01) and significantly decreased the internal flexion moment of the knee joint (P<0.01). INTERPRETATION: These results suggest an important link between the kinematic/kinetic parameters of the lower-limb joints and the plantarflexion resistive moment of an articulated ankle-foot orthosis. A future study should be performed to clarify their relationship further so that the practitioners may be able to use these parameters as objective data to determine an optimal plantarflexion resistive moment of an articulated ankle-foot orthosis for improved orthotic care in individual patients.